HUBUNGAN EFIKASI DIRI DAN MOTIVASI BERPRESTASI SISWA SMA WAHYU MAKASSAR - Nur Febri Sari; M. Ahkam; Wilda Ansar (CV. ADIBA AISHA AMIRA, 2024)
Students who have high self-confidence will have high motivation to achieve as well, and can support students in achieving academic achievement or certain goals. Meanwhile, students who have low self-confidence will have an impact on their low motivation as well, so students cannot achieve academic achievement as expected. This study uses a quantitative approach with a correlation method. This study uses a quantitative approach with a correlation method. This research method uses a quantitative approach with the correlation method The subjects in this study are all students of Wahyu Makassar High School which totals 72 students, who are in classes X and XI and there are 2 fields of majors. The analysis technique used in hypothesis testing is Spearman rank correlation. The results of the study showed that there was a positive relationship between self-efficacy and achievement motivation of Wahyu Makassar High School students with a correlation value of0.509 and a significance of 0.00. This means that the higher the self-efficacy, the higher the motivation for achievement in students. On the other hand, the lower the self-efficacy, the lower the self-motivation in students at Wahyu Makassar High School. The results of this research can be an evaluation material for students to increase self-efficacy by building confidence and developing social skills.